Clinical application in sexual orientation - Binti Mustamam, Dayana Musfirah; A/L Rajathurai, Jivanishenthiran; Gusdian, Putri Milenia; Binti Nasir Khan, Zaireen Zulaika (ProGCouns: Journal of Professionals in Guidance and Counseling, 2020)
When we talk about sexual orientation the first think that come into our mind is on the individual's sexual identity in relation to the gender. But, we should know that sexual orientation and sexual identity are different. Sexual orientation is also generally defined in terms of several groups, such as heterosexuals, where there is psychological, romantic or sexual attraction towards the opposite sex, homosexuals like gay or lesbian with a psychological, social or sexual preference towards the same sex. This paper is one of the assignments in the Multicultural Counseling's subject, which discusses several cases that discuss about client's sexual orientation, then the causes and impacts of the social environment on their sexual orientation. As we know, this problem is a thing that not consider in majority of environment. Also, we convey how future counselors should respond and behave when dealing with sexual orientation clients.